Filamer Christian College and its role in the advancement of Christian education, 1904-2003. - Lamason, Liza Lyn S. (2002.)
This paper is a study on the history of Filamer Christian College and its role in the advancement of Christian eduacation from 1904 to 2001. Primarily this study aims to: (1)identify the factors and events that led to the founding of FCC; (2)trace the development of FCC from its establishment up to the present (2001) in terms of administrators and movers, building construction, facilities and equipment, curricula and academic disciplines, student and faculty population, goals, visions, programs and services; and (3)determine the role of FCC in the advancement of Christian education by identifying the school's distinctive features as a proponentof the said religious instruction. Data needed for the study came from records, documents and other materials found in several offices of FCC. Interviews with several former as well as present faculty and staff members of FCC were done for other supplemental information. The study revealed that FCC began in 1904 as a humble home school founded by American Baptist missionaries, Rev. Joseph and Effie Robbins, which provided shelter and training for orphaned children. Since then, the school developed to become an academic institution offering complete educational training from kindergarten to graduate studies and at the same time providing services and porgrams to better serve the needs of the students. Christian education has always been an important element in FCC's mode of instruction. Christian education is evident in the school's programs (such as Bible studies, convocations, and the CEW celebration0, curriculum (with Bible as one required subject for college students) and religious organizations. The diversity of religious backgrounds of both faculty and students coupled with an inadequate budget due to financial constraints have hindered school to become more effective in its thrust for the advancement of Christian education. Based on the findings of the study, the following recommendations are endorsed: (1) that the study on the history and development of FCC be continously updated; (2) that a study be made on the impact of Christian education to students and to the community so as to gauge whether FCC is effective in its role of advancing christian education; and (3) that a study on the influence of FCC to the development of roxas City will also be an interesting offshoot of this research.
Research Project (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Christian Education